ANALYSIS OF A LIFECYCLE OF PROJECTS IN PROPERTY DEVELOPMENT BUSINESS - Gennady A. Kurushin (Статистика и экономика, 2016)
Analysis of lifecycles allows forming a good understanding of business success factors. Analysis of the lifecycles of this specific business area which is real estate projects is given in the article. This area is of a high interest in the view of management, because of its high economic importance and specific character of project activities.